2023
DOI: 10.1038/s41467-023-36783-8
|View full text |Cite
|
Sign up to set email alerts
|

Turning dead leaves into an active multifunctional material as evaporator, photocatalyst, and bioplastic

Abstract: Large numbers of leaves fall on the earth each autumn. The current treatments of dead leaves mainly involve completely destroying the biocomponents, which causes considerable energy consumption and environmental issues. It remains a challenge to convert waste leaves into useful materials without breaking down their biocomponents. Here, we turn red maple dead leaves into an active three-component multifunctional material by exploiting the role of whewellite biomineral for binding lignin and cellulose. Owing to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Energy is important for human life, stimulating intensive efforts to achieve efficient energy conversion and utilization. 1–4 The conversion of clean and renewable solar energy to electricity with solar cells is one of the promising technologies to address energy and environmental issues. Among the third generation of photovoltaic cell technologies, dye-sensitized solar cells (DSSCs) and perovskite solar cells (PSCs) have prompted intensive research and development due to their low cost, environmental friendliness, and flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Energy is important for human life, stimulating intensive efforts to achieve efficient energy conversion and utilization. 1–4 The conversion of clean and renewable solar energy to electricity with solar cells is one of the promising technologies to address energy and environmental issues. Among the third generation of photovoltaic cell technologies, dye-sensitized solar cells (DSSCs) and perovskite solar cells (PSCs) have prompted intensive research and development due to their low cost, environmental friendliness, and flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the purification of lignocellulose for film fabrication necessitates intricate procedures, and the usually applied types are cellulose nanocrystals or cellulose nanofibrils, which require copious amounts of chemicals and energy, thus significantly reducing the sustainability of the lignocellulose film (Table S1). Aside from cellulose sourced from wood, some bacterial species can produce cellulose, termed bacterial cellulose (BC). , Unlike lignocellulose, pure cellulose can be obtained easily from BC without any chemical treatments since it does not mix with hemicellulose, lignin, and pectin . Meanwhile, BC has other advantages over lignocellulose, including high barrier properties, high crystallinity, excellent mechanical properties, three-dimensional (3-D) network structure, and strong degradability, which make it the most promising candidate to replace petroleum-based packaging material.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of the TW with inherent directional channels as an optical waveguide for achieving a directional light concentration within an LSC is an interesting concept. Additionally, lignin derived from wood contains an abundance of phenylpropane structural units and diverse oxygen-containing functional group structures, making it an ideal precursor for the synthesis of CQDs. , Numerous studies have demonstrated that by adopting a doping strategy, lignin-based CQDs (L-CQDs) can be obtained, which exhibit a high fluorescence quantum yield (QY) and a large Stokes shift. Consequently, L-CQDs can be considered promising fluorescent materials for constructing LSCs. , …”
Section: Introductionmentioning
confidence: 99%